2021
DOI: 10.3390/v13122515
|View full text |Cite
|
Sign up to set email alerts
|

Role of HSV-1 Capsid Vertex-Specific Component (CVSC) and Viral Terminal DNA in Capsid Docking at the Nuclear Pore

Abstract: Penetration of the viral genome into a host cell nucleus is critical for initiation of viral replication for most DNA viruses and a few RNA viruses. For herpesviruses, viral DNA ejection into a nucleus occurs when the capsid docks at the nuclear pore complex (NPC) basket with the correct orientation of the unique capsid portal vertex. It has been shown that capsid vertex-specific component (CVSC) proteins, which are located at the twelve vertices of the human herpes simplex virus type 1 (HSV-1) capsid, interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Studies using time-lapse microscopy have shown that HSV-1 undergoes rapid axonal flow in both directions [29,30]. After the nucleocapsid is transported to the surrounding area of the nucleus, it can interact with the nuclear pore complex, and then dsDNA is injected into the nucleus through the nuclear pore [31]. Subsequently, the nucleocapsid is transported towards the nucleus via microtubules.…”
Section: The Process Of Hsv-1 Entering Host Cells Replication and Ass...mentioning
confidence: 99%
“…Studies using time-lapse microscopy have shown that HSV-1 undergoes rapid axonal flow in both directions [29,30]. After the nucleocapsid is transported to the surrounding area of the nucleus, it can interact with the nuclear pore complex, and then dsDNA is injected into the nucleus through the nuclear pore [31]. Subsequently, the nucleocapsid is transported towards the nucleus via microtubules.…”
Section: The Process Of Hsv-1 Entering Host Cells Replication and Ass...mentioning
confidence: 99%
“…After the nucleocapsid is transported to the surrounding area of the nucleus, it can interact with the nuclear pore complex, and then, dsDNA is injected into the nucleus through the nuclear pore [ 39 ]. DNA viruses, such as herpesviruses, replicate in specific inclusions within the nucleus.…”
Section: The Replication Process Of the Virus Within The Cellmentioning
confidence: 99%
“… 110 After binding to the cell surface, the HSV envelope fuses with the host plasma membrane, delivering the unenveloped virus, that is, the tegumented capsid, into the cytoplasm 111 . After losing the tegument, the capsid is transported into the nucleus, 112 where transcription and replication take place 113 . The newly assembled capsids are transported from the nucleus into the cytoplasm, in which they acquire the tegument and the envelope at the Golgi, before being transported toward the cell periphery for exit and spread 114,115 …”
Section: Viral Hijacking Of Kinesinsmentioning
confidence: 99%